2020
DOI: 10.3126/jpn.v10i2.27267
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-thyroid peroxidase antibody in infertile Nepalese women: a hospital-based study

Abstract: Background: Infertility is a critical component of reproductive health that can precipitate agony for a couple. Antibodies against thyroid peroxidase can lead to not only autoimmune thyroiditis which is highly prevalent in women, but may also represent a generalized autoimmune milieu in our body that can be associated with infertility. This study aims to assess anti-thyroid peroxidase antibodies in female patients with infertility. Materials and Methods: This is a cross-sectional study carried out in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…In context of the studies in pregnant population, Kiran et al reported thyroid peroxidase antibodies and anti-thyroglobulin antibodies positive rates in 66.4% and 52.1% respectively [ 45 ]. Similar studies in different cohorts in Nepal by Chaudhary et al [ 25 ] reported anti-TPO positivity in pregnant women to be 3.26% while Tuladhar et al [ 46 ] reported 7.4% anti-TPO positivity in infertile females.…”
Section: Discussionsupporting
confidence: 65%
“…In context of the studies in pregnant population, Kiran et al reported thyroid peroxidase antibodies and anti-thyroglobulin antibodies positive rates in 66.4% and 52.1% respectively [ 45 ]. Similar studies in different cohorts in Nepal by Chaudhary et al [ 25 ] reported anti-TPO positivity in pregnant women to be 3.26% while Tuladhar et al [ 46 ] reported 7.4% anti-TPO positivity in infertile females.…”
Section: Discussionsupporting
confidence: 65%